Peripheral blood stem cell transplantation vs. bone marrow transplantation for aplastic anemia: a systematic review and meta-analysis - Zhang, Zhao; Zhou, Xianghui; Cheng, Zhipeng; Hu, Yu (Frontiers in Medicine, 2023)
Background Hematopoietic stem cell transplantation (HSCT) is an effective treatment for aplastic anemia. Recently, peripheral blood stem cell transplantation (PBSCT) has gradually replaced traditional bone marrow transplantation (BMT). However, which graft source has a better therapeutic effect and prognosis for aplastic anemia (AA) remains unclear. Therefore, we conducted this systematic review and meta-analysis. Methods We systematically searched PubMed, EMBASE, and the Cochrane Library without language limitations for studies using PBSCT or BMT for AA. Data were analyzed using the Open Meta-Analyst. Results We identified 17 of 18,749 studies, including seven comparative reports and nine single-arm reports, with a total of 3,516 patients receiving HSCT (1,328 and 2,188 patients received PBSCT and BMT, respectively). The outcomes of the comparative studies showed similar 5-year overall survival [OS; relative risk (RR) = 0.867; 95% confidence interval (CI), 0.747–1.006], similar transplant-related mortality (RR = 1.300; 95%CI, 0.790–2.138), graft failure rate (RR = 0.972; 95%CI, 0.689–1.372) between the PBSCT group and the BMT group, while the PBSCT group had a significantly higher incidence of chronic graft-versus-host disease (GVHD; RR = 1.796; 95% CI, 1.571–2.053) and a higher incidence of grade IV acute GVHD (RR = 1.560; 95% CI, 1.341–1.816) compared to the BMT group. The outcomes of single-arm reports showed similar 3-year OS and incidences of chronic GVHD, acute II–IV GVHD, III–IV GVHD, transplant-related mortality and graft failure rate between PBSCT and BMT. Conclusion Before 2010, PBSCT was not superior to BMT in terms of 5-year OS, transplant-related mortality and graft failure rate, but it exhibited a higher risk of both chronic and acute GVHD. After 2010, PBSCT and BMT showed similar 3-year OS, GVHD risks, transplant-related mortality and graft failure rate. PB grafts are more suitable for HSCT of the AA for convenience and pain relief. Systematic review registration www.crd.york.ac.uk/PROSPERO/, CRD42023412467.